STATE REGULATION OF PENSION ACCUMULATION ELEMENT: FOREIGN EXPERIENCE (on Example of Sweden and Germany) - Vereshchak V.M. (Pressing Problems of Public Administration, 2016)
In the article the peculiarities of state regulation of the savings element of pension systems in Swedenand Germany.